Comparison of ilioinguial/iliohyphogastic nerves block with wound-infiltration on postoperative pain – a randomised controlled trial - Khan, Robyna Irshad; Hameed, Malika; Ali, Summaiya Ahsan (Journal of the Pakistan Medical Association, 2024)
Objective: To compare postoperative pain scores at rest and on movement in patients undergoing open inguinal hernia repair between those receiving illioinguinal/illiohypogastric nerve block with ropivacaine or wound infiltration with ropivacaine. Method: The randomised clinical trial was conducted at the Department of Anaesthesiology, Aga Khan University Hospital a tertiary care centre from March to August 2019 and comprised patients of either gender scheduled for elective unilateral open inguinal hernia repair under general anaesthesia. They were randomised into illioinguinal/illiohypogastric nerve block group A, and wound infiltration group B. In group A, 20ml of 0.25% ropivacaine was infiltrated in the vicinity of the nerves under ultrasound guidance, while group B received wound infiltration with ropivacaine 10ml 0.25% at the end of surgery. Postoperative static and dynamic pain was assessed at 0, 2, 6, 12 and 24 hours using visual analogue scale. Total usage of opioids in 24 hours postoperatively in both groups, patient satisfaction and complications were recorded. Data was analysed using SPSS 19. Results: Of the 60 patients, 30(50%) were in each of the 2 groups. There were 29(96.7%) males and 1(3.3%) female in group A with mean age 45.63±17.43 years, and 28(93.3%) males and 2(6.7%) females in group B with mean age 49.33±15.39. The mean pain score at rest was not significantly different between the groups (p>0.05). On movement, the mean pain score between the groups was different only at 6 hours (p=0.02). There were no significant intergroup difference in total usage of opioids in 24 hours postoperatively and patient satisfaction (p>0.05). Conclusion: Illioinguinal/illiohypogastric nerve block and wound infiltration with ropivacaine were found to be equally effective methods in controlling postoperative pain. ClinicalTrials.gov ID: NCT04462510. Key Words: Local anaesthesia, Inguinal hernia, Pain management, Patient satisfaction.